Improving Tourist Attraction Quality at Tiga Warna Beach Malang, East Java - Reza Akbar Satriayudha (Catuspata Press, 2021)
Abstract: Purpose: This paper is to find out the green tourism application on Tiga Warna Beach, Malang, East Java, Indonesia, with SWOT (strengths, weaknesses, opportunities, and threats) analysis. Research methods: This research uses qualitative descriptive method and is done by observing the existence and situation that happens in the field of research and studying some related literatures. Findings: Tiga Warna Beach is a beautiful and attractive destination for tourists but some restrictions make this beach less crowded every day. Tourists who visit are satisfied with the natural beauty served. The final results of development strategies are based on the analysis of SWOT. Implication: A macro business perspective is required for Tiga Warna Beach. Local people and the government should work together by focusing on the common benefits of the destination rather than on opportunistic objectives.